2014
DOI: 10.1080/00150193.2013.849518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sintering Temperature on Nanocrystalline Non-stoichiometric Sr0.8Bi2.2Ta2O9Ferroelectric Ceramics

Abstract: In the present work, nanocrystalline non-stoichiometric strontium bismuth tantalate (SBT) of composition Sr 0.8 Bi 2.2 Ta 2 O 9 was synthesized by mechanical activation technique using a high energy planetary ball mill. The synthesized powder was sintered at different sintering temperature i.e. 1050 • C, 1100 • C, 1150 • C. X-ray diffractograms reveal the formation of single phase layered perovskite structure in all samples sintered at various temperatures. Scanning electron microscopy (SEM) and Transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, photocatalytic water splitting is sensitive to the deposition methods of co-catalysts. Kudo et al reported that photocatalysts show diversity in photocatalytic water splitting with different deposition methods [59]. Moreover, transition-metal sulfides like MS (M = Ni, Co, Cu) have also been developed as cocatalysts to improve the photocatalytic activity.…”
Section: Co-catalyst Surface Modificationmentioning
confidence: 99%
“…In addition, photocatalytic water splitting is sensitive to the deposition methods of co-catalysts. Kudo et al reported that photocatalysts show diversity in photocatalytic water splitting with different deposition methods [59]. Moreover, transition-metal sulfides like MS (M = Ni, Co, Cu) have also been developed as cocatalysts to improve the photocatalytic activity.…”
Section: Co-catalyst Surface Modificationmentioning
confidence: 99%